Hubungan Stres Kerja dengan Self-Reported Quality of Care pada Perawat di RSUD dr. H. Chasan Boesorie Kota Ternate - Takyan Safira Hakim; Novi Elisadevi (Jurnal Ragam Pengabdian, 2026)
Work stress is one of the psychological factors that may influence the quality of nursing care in hospitals. High workload, shift systems, and emotional demands in patient care may increase nurses’ work stress and affect the quality of care provided. This study aimed to examine the relationship between work stress and self-reported quality of care among nurses at RSUD Dr. H. Chasan Boesorie, Ternate. This research employed a quantitative approach with a descriptive correlational design and cross-sectional method. The population consisted of 312 nurses, with a sample of 185 respondents selected using Slovin’s formula and simple random sampling technique. Data were collected using five-point Likert scales to measure work stress and Self-reported quality of care. Data were analyzed using Pearson correlation and simple linear regression with SPSS 25.0. Reverse scoring was applied to the self-reported quality of care variable, where higher scores indicate lower quality of care. The results showed a significant relationship between work stress and self-reported quality of care (r = 0.879; p < 0.05). Regression analysis indicated that work stress contributed 77.3% to the variance in self-reported quality of care among nurses.  It can be concluded that work stress has a very strong influence on the perceived quality of nursing care. Therefore, stress management strategies are needed to improve hospital service quality.